The development of speech acts through group work interaction among students of tenth year a at Colegio de bachillerato 27 de Ferrero of the city of Loja during the 2016-2017 school year - Gaona Avila, Jenny Maribel (2018)
The objective of the research was to develop speech acts through group work interaction among students of tenth year A at Colegio de Bachillerato 27 de Febrero of the city of Loja during 2016-2017 school year. The scientific, descriptive and synthetic-analytical methods were used to analyze and describe the results of the research. The instruments applied to collect the data were tests and questionnaires applied to the students before, during and after the intervention plan. The results showed that students developed satisfactorily the knowledge in speech acts and their academic level in English increased. In conclusion, the use of group work interaction strategy was effective since most of students can communicate appropriately. Learners also increased their interaction among them, and their relationship improved a lot. They were not afraid to share their opinions and their participation was active in the development of every task, using speech acts suitably.